Edukasi Ibu Hamil Tentang Pencegahan Stunting di PMB Elvi Tiana, Amd. Keb Kota Batam - Susanti Susanti; Khusnul Makrifatus Sholikhah; Elvi Tiana; Revi Anggraini; Aina Aina (PPNI UNIMMAN, 2023)
Stunting is a nutritional problem caused by a long-term lack of nutrition during the first 1000 days of life (HPK), which is a critical period. thus resulting in growth disorders in children, namely the child's height is lower or shorter (dwarf) than the standard age. The purpose of this study is to provide education to pregnant women about stunting prevention at PMB Elvi Tiana, Amd.Keb. The method used in this activity is a community service focus group discussion with an interactive question-and-answer lecture between the servant and pregnant women which lasts for 40 minutes. The number of pregnant women participating in community service is 20 pregnant women. Before the educational activity was carried out, a pre-test was given and after the activity, a post-test was given using a questionnaire instrument containing 20 questions about the knowledge of pregnant women about stunting prevention. The results from the Pre Test table and Post Test table can be concluded that there is an increase in Mother's knowledge about stunting prevention before and after community service is carried out for 20 pregnant women.